Genomic analysis identifies frequent deletions of Dystrophin in olfactory neuroblastoma. Issue 1 (December 2018) - Gallia, Gary; Zhang, Ming; Ning, Yi; Haffner, Michael; Batista, Denise; Binder, Zev; Bishop, Justin; Hann, Christine; Hruban, Ralph; Ishii, Masaru; Klein, Alison; Reh, Douglas; et al.
Abstract Olfactory neuroblastoma (ONB) is a rare malignant neoplasm arising in the upper portion of the sinonasal cavity. To better understand the genetic bases for ONB, here we perform whole exome and whole genome sequencing as well as single nucleotide polymorphism array analyses in a series of ONB patient samples. Deletions involving the dystrophin (DMD ) locus are found in 12 of 14 (86%) tumors. Interestingly, one of the remaining tumors has a deletion inLAMA2, bringing the number of ONBs with deletions of genes involved in the development of muscular dystrophies to 13 or 93%. This high prevalence implicates an unexpected functional role for genes causing hereditary muscular dystrophies in ONB. Olfactory neuroblastoma (ONB) is a rare malignant tumor whose genetic basis is poorly understood. Here the authors identify recurrent deletions involving dystrophin in the majority of ONB patient tumors examined.